PENTINGNYA PEMAHAMAN AJARAN GERAKAN ZAMAN BARU TERHADAP PEMAHAMAN JEMAAT DI GSJPDI VICTORY PRAJEKAN MENURUT 1 YOHANES 5 : 19-21 - Natalia, Yosefin; Mintodihardjo, Subagio; Susanto, Yusak Noven (Alucio Dei, 2025)
In today's postmodern era, the powerful emergence of the New Age Movement (NAM) is unmistakable. This research seeks to delve deeper into the phenomenon of NAM within the congregational context of GSJPDI Victory Prajekan. Employing a descriptive qualitative approach, the study gathered data through observation, in-depth interviews, and documentation, revealing NAM as a complex and influential force in modern society. While NAM offers numerous benefits and incorporates spiritual and religious elements from various traditions neutrally and flexibly, it permeates all aspects of human life without seeming to contradict the Bible. A thorough analysis of 1 John 5:19-21 uncovers parallels between NAM teachings and historical heresies, particularly in spiritual practices at odds with the Christian faith, such as yoga. This research underscores the crucial need for a deep understanding of the Bible to navigate the challenges of modern spirituality within the congregation. The lack of such knowledge can lead the congregation astray, embracing practices incompatible with their Christian faith. Consequently, the church must prioritize comprehensive biblical education to equip the congregation to effectively counter NAM's influence. Keyword: GZB; New Age Movement; 1 John 5:19-21; Spirituality; Yoga; Mysticism.